Kontekstualisasi Mazmur Pujian dengan Lantunan Foruk dalam Ibadah Etnis Jemaat GPM Adodo Fordata - Hendriks, Glenn Victor (Program Pascasarjana UKIM, 2024)
Singing is an important element of congregational worship. Singing with the right meaning and appreciation has an impact on the development of the people. A song must be based on the local context of the congregation. Herein lies the importance of contextualizing congregational singing. One form of song contextualization is by using ethnic songs in congregational worship. Ethnic songs describe the congregation's local characteristics and are the congregation's identity. Using a qualitative research method, this study aims to find the form of ethnic songs that can be sung in the worship of the GPM Adodo Fordata congregation. In addition, this research also uses the juxtaposition method to juxtapose two forms of singing, namely, psalms and foruk. This research data was obtained from participant observations when the author was the Chairman of the Congregation Assembly for 6 years and interviews with cultural experts in Tanimbar. This research proves that as a form of contextual singing, foruk can be sung as psalms in congregational worship. The application of foruk as psalms is able to help people to live and interpret worship.